2021
DOI: 10.3390/su132413590
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Damage of Climbing Activity on Sandstone Lichen Cover

Abstract: Climbing activities affect cliff site species. With cliff sites harbouring unique species communities, the rise in popularity of outdoor climbing activities is a major threat. In this study, we assessed a previously unclimbed boulder before, during and after 500 climbing ascents. We observed an overall reduction in lichen cover by 4.2–9.5%, located around the footholds and combined foot- and handhold but not the handhold. We found the reduction in lichen cover to be strongest at the very start of the climbing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…This decrease is equivalent to the loss of around two plant individuals per climbing ascent, mostly occurring during the first 10 climbers' ascents. This is in line with the results of Schweizer et al (2021), which revealed that climber impacts occur mostly during the climbers' first ascents. Climbing outfitters typically remove loose rocks that might pose a safety risk for climbers.…”
Section: The Origin and Extent Of Climbing Impactsupporting
confidence: 92%
See 1 more Smart Citation
“…This decrease is equivalent to the loss of around two plant individuals per climbing ascent, mostly occurring during the first 10 climbers' ascents. This is in line with the results of Schweizer et al (2021), which revealed that climber impacts occur mostly during the climbers' first ascents. Climbing outfitters typically remove loose rocks that might pose a safety risk for climbers.…”
Section: The Origin and Extent Of Climbing Impactsupporting
confidence: 92%
“…Significant differences in lichen cover were observed after 20 ascents compared to the pre-opening monitoring, and after 30 ascents compared to the post-opening monitoring, resulting in an overall reduction of 34.6%. These findings also align with the results of Schweizer et al (2021), who reported a strong reduction in lichen cover within the first 50 ascents, with no significant decreases afterwards. However, lichen cover was constant in the nearby area of the climbing route (Fig.…”
Section: The Origin and Extent Of Climbing Impactsupporting
confidence: 91%
“…Also, first ascents could be more impactful for cliff plant communities. Thus, the impact would not increase significantly with increasing frequency of climbers, as indicated by Schweizer et al (2021). They studied how lichen cover in a boulder changes during simulated increasing climbing frequency.…”
Section: Climbing Impact On the Presence And Diversity Of Speciesmentioning
confidence: 99%